Pengaruh edukasi ROM aktif kombinasi media booklet dan demonstrasi terhadap kemampuan mobilisasi pada pasien post operasi fraktur - Al Murhan; Adelia Putri; Siti Fatonah (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2022)
Background: Fractures are the case with the highest incidence of the 10 most cases found in General Ahmad Yani Metro Hospital. Patients with a diagnosis of fracture often experience pain and impaired physical mobility. Patients were given health education about Range Of Motion (ROM) without using media. Objective: To determine the effect of active ROM education in combination with booklet media and demonstration on the ability to mobilize in postoperative fracture patients. Methods: The design of this research is quasi-experimental and quantitative type. The population is post-fracture patients at RSUD Jendral Ahmad Yani Metro in 2021, with a sample of 32 respondents. Analysis with Independent T test. Research time is from 01 June to 17 July 2021. Results: The average mobilization ability in the experimental group with active ROM education combined with booklet and demonstration media was 17.19, while the average mobilization ability in the control group (without active ROM education combined with booklet and demonstration media) was 14.88. The results of the analysis show the results of -value = 0.04. Conclusion: There is a significant effect of active ROM education therapy with a combination of booklet and demonstration media on the ability to mobilize in post-fracture patients, where the level of mobilization ability in the group with active ROM education with a combination of booklet and demonstration media is higher than in patients who are not given active ROM education with a combination of media. booklets and demonstrations. Suggestion: It is recommended that the active ROM education program with a combination of booklets and demonstration media can be given to every special surgical treatment room at the hospital. Pendahuluan: Fraktur menjadi kasus dengan angka kejadian tertinggi dari 10 kasus terbanyak yang ditemui di RSUD Jendral Ahmad Yani Metro. Pasien dengan diagnosa fraktur sering mengalami nyeri dan hambatan mobilitas fisik. Pasien diberikan edukasi kesehatan mengenai ROM tanpa menggunakan media. Tujuan: Untuk mengetahui pengaruh edukasi ROM aktif kombinasi media booklet dan demonstrasi terhadap kemampuan mobilisasi pada pasien post operasi fraktur. Metode: Desain penelitian ini dengan quasy eksperimen dan jenis kuantitatif. Populasi adalah pasien post fraktur di RSUD Jendral Ahmad Yani Metro tahun 2021, dengan sampel sebanyak 32 responden. Analisis dengan uji T test Independen. Waktu penelitian mulai 01 Juni sampai 17 Juli 2021. Hasil: Menunjukkan rata-rata kemampuan mobilisasi pada kelompok eksperimen dengan edukasi ROM aktif kombinasi media booklet dan demonstrasi adalah 17,19, sedangkan rata-rata kemampuan mobilisasi pada kelompok kontrol (tanpa edukasi ROM aktif kombinasi media booklet dan demonstrasi) adalah 14,88. Hasil analisis menunjukkan hasil ρ-value = 0,04. Simpulan: Ada pengaruh yang signifikan terapi edukasi ROM aktif kombinasi media booklet dan demonstrasi terhadap kemampuan mobilisasi pada pasien post fraktur, dimana tingkat kemampuan mobilisasi pada kelompok yang edukasi ROM aktif kombinasi media booklet dan demonstrasi lebih tinggi daripada pasien yang tidak diberikan edukasi ROM aktif kombinasi media booklet dan demonstrasi. Saran: Sebaiknya program edukasi ROM aktif kombinasi media booklet dan demonstrasi ini bisa diberikan pada setiap ruangan perawatan bedah kusus rumah sakit.